Analysis of MHD Williamson micropolar fluid flow in non-Darcian porous media with variable thermal conductivity. (August 2022) - Mishra, Pankaj; Kumar, Dhirendra; Kumar, Jogendra; Abdel-Aty, Abdel-Haleem; Park, Choonkil; Yahia, Ibrahim S.
Abstract: The purpose of this research is to investigate the MHD flow of Williamson fluid through a non-Darcy porous medium with micro-rotation. The governing equations are first converted into a coupled system of ODEs with initial and boundary conditions. The shooting procedure with the Runge-Kutta method is used to solve the ODEs, and determine the impact of various parameters for heat and momentum transfer of boundary layer flow. Finally, all findings are graphed and compared with earlier results to ensure that the current outputs are perfectly valid. Furthermore, it can be seen from the characteristic graph that the system parameters, magnetic field M and non-Darcy F tend to reduce the fluid velocity. Also, a comparison between the two fluid models, Williamson fluid and micropolar fluid have been obtained via the effects of various parameters on skin friction and Nusselt number.